THE ADMINISTRATION OF MUSLIM’S AND NON-MUSLIM’S OWNERLESS ESTATE (BONA VACANTIA) IN WEST MALAYSIA: AN ANALYSIS - Akmal Hidayah Halim; Tajul Aris Bin Ahmad Bustami; Wan Noraini Binti Mohd Salim; Rahmawati Mohd Yusoff, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
In Malaysia, if a deceased passed away intestate (without leaving a valid will) and no next of kin is available, his or her estate is deemed as an ownerless estate (bona vacantia). However, bona vacantia has not been classified, identified, and examined clearly, particularly in terms of the various sets of law applicable to the non-Muslims and Muslims in West Malaysia. Therefore, this paper intends to examine the classification of estates categorised under bona vacantia, its position in both Islamic law and Malaysian law, and the issues associated with the topic. The doctrinal analysis is adopted by analysing the current primary and secondary materials which include case law, statutory provisions, and other legal and non-legal literature. Consequently, the administration of bona vacantia is found to be governed by different procedures and laws, based on the personal law of the deceased. If he is a Muslim, his estate will be reverted to Baitulmal. Meanwhile, the type of estate left by a deceased non-Muslim will determine the reversion of such estate, either to the Government or the State Authority.